Prehospital Pain Management: Disparity By Age and Race. (4th March 2018) - Hewes, Hilary A.; Dai, Mengtao; Mann, N. Clay; Baca, Tanya; Taillac, Peter
Abstract: Importance : Historically, pain management in the prehospital setting, specifically pediatric pain management, has been inadequate despite many EMS (emergency medical services) transports related to traumatic injury with pain noted as a symptom. The National Emergency Services Information System (NEMSIS) database offers the largest national repository of prehospital data, and can be used to assess current patterns of EMS pain management across the country. Objectives : To analyze prehospital management of pain using NEMSIS data, and to assess if variables such as patient age and/or race/ethnicity are associated with disparity in pain treatment. Design/Setting/Participants : A retrospective descriptive study over a three-year period (2012–2014) of the NEMSIS database for patients evaluated for three potentially painful medical impressions (fracture, burn, penetrating injury) to assess the presence of documented pain as a symptom, and if patients received treatment with analgesic medications. Results were analyzed according to type of pain medication given, age categories, and race/ethnicity of the patients. Main outcomes : Percentage of EMS transports documenting the three painful impressions that had pain documented as a symptom, received any of the six pain medications, and the disparity in documentation and treatment by age and race/ethnicity. Results : There were 276, 925 EMS records in the NEMSIS database that met inclusion criteria. Pain was listed as a primary or associated symptom for 29.5% of patients, and the youngest children (0–3 years) were least likely to have pain documented as a symptom (14.6%). Only 15.6% of all activations documented the receipt of prehospital pain medications. Children (<15 years) received pain medication 14.8% [95% CI 14.33, 15.34] of the time versus adults (≥15 years) 15.6% [95% CI 15.48, 15.76, p = 0.004]. Morphine and fentanyl were the most commonly administered medications to all age groups. Black patients were less likely to receive pain medication than other racial groups. Conclusions : Documentation of pain as a symptom and pain treatment continue to be infrequent in the prehospital setting in all age groups, especially young children. There appears to be a racial disparity with Black patients less often treated with analgesics. The broad incorporation of national NEMSIS data suggests that these inadequacies are a widespread challenge deserving further attention.